The Reception of the Medieval Galician-Portuguese Lyrical Poetry in Argentina. "Morriña" and Scholarship on the Other Side of the Atlantic Ocean - del Rio Riande, Gimena (Madrygal. Revista de Estudios Gallegos, 2017)
The aim of this work is to give account of the different ways that the unfortunate Spanish Thirties Decade impacted, through the exiled, on the Argentina society and culture, and established a different canon regarding the European editions of the Galician-Portuguese lyrical poetry. To achieve this, it revises the Forties and Fifties publishing scene on the topic in Buenos Aires. On the one hand, the early medieval Galician poetry anthology Poesía gallega medioeval de los siglos XII al XV, published by Emecé in Buenos Aires just after the Spanish Civil War (1941) by an undercover Luís Seoane in the collection founded by him, Dorna, can be seen as a milestone in relation to the circulation and reception of the Galician-Portuguese lyrical poetry out of Spain. This first step, followed by the edition of some cantigas in Francisco Luís Bernárdez’s 1952 Florilegio de la Biblioteca Vaticana, and in certain publications of the Galician Center in Buenos Aires, seems to be based on a feeling of morriña of who is far from home. Anyway, this process will turn into scholarship with the work of Claudio Sanchez Albornoz, president of the Spanish Republic in the exile. Sanchez Albornoz will open a new period for the studies on Spain and Galicia and the Galician-Portuguese lyrical poetry in Argentina. An interesting fact is that in the timeline the articles proposes, we will discover that it was in this country where the first anthology about the Galician-Portuguese lyrical poetry was published.